Hospital Social Workers' Boundary Work in Paediatric Acute Wards—Competitive or Collaborative?. (30th October 2021) - Mannsåker, Ida Krag-Rønne; Vågan, André; Geirdal, Amy Østertun; Stenberg, Una
Abstract: Recent research suggests that the notion of boundary work can improve our understanding of interprofessional tension and collaboration in health care, yet hospital social workers (HSWs) have not received sufficient attention in this area. Using boundary work as a theoretical framework, this article investigates HSWs' boundary work in interactions with other health care professionals in paediatric acute wards. The data were based on in-depth interviews with nineteen HSWs at hospitals in Norway about their experiences with interprofessional collaboration. Based on their situated narratives, abductive analysis was performed, using the conceptually distinct but inter-related forms of competitive and collaborative boundary work that are grounded in Abbott's framework of jurisdiction. The findings demonstrate how HSWs construct, defend and extend boundaries to create distinctions between themselves and others, and how they sometimes adapt and downplay boundaries in order to achieve common goals and perform their work. As a facilitator of this process, the HSW might be viewed as a boundary subject. This, in turn, can result in optional and intentional ways for HSWs to carry out boundary work. There is reason to believe that, the less specific educational requirements and role guidelines, the more important these mechanisms become. Abstract : Hospital social workers (HSWs) collaborate with various professionals in order to strengthen patients' health outcomes. We know a lot about the different roles and tasks they perform. However, less is known about how HSWs create distinctions between themselves and other professionals. To explore this, we conducted individual interviews with nineteen HSWs about their experiences with interprofessional collaboration. Their accounts of interactions are valuable for understanding their boundary work. The findings demonstrate how they construct, defend and extend boundaries to create distinctions between themselves and others and how they simultaneously adapt and downplay boundaries in order to achieve common goals. Increasing knowledge of these mechanisms can strengthen HSWs' ability to influence existing structures and discourses within a health context. The less specific the educational requirements and common guidelines, the more important these mechanisms become.